2021
DOI: 10.1007/s00125-021-05557-6
|View full text |Cite|
|
Sign up to set email alerts
|

Neuron-specific biomarkers predict hypo- and hyperalgesia in individuals with diabetic peripheral neuropathy

Abstract: Aims/hypothesis The individual risk of progression of diabetic peripheral neuropathy is difficult to predict for each individual. Mutations in proteins that are responsible for the process of myelination are known to cause neurodegeneration and display alteration in experimental models of diabetic neuropathy. In a prospective observational human pilot study, we investigated myelin-specific circulating mRNA targets, which have been identified in vitro, for their capacity in the diagnosis and predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 36 publications
2
45
1
Order By: Relevance
“…It is therefore conceivable that the significantly lower MTR values identified in people with RRMS in the sciatic nerve (but not the lumbar plexus) in this study could be indicative of peripheral codemyelination, which is also in line with previous findings (3). Further multi-modal investigations may be needed to confirm the pathophysiological basis of the alterations in MTR identified in this study, for example with the use of diffusion-weighted imaging, as demonstrated in previous studies of peripheral neuropathy (29)(30)(31).…”
Section: Discussionsupporting
confidence: 87%
“…It is therefore conceivable that the significantly lower MTR values identified in people with RRMS in the sciatic nerve (but not the lumbar plexus) in this study could be indicative of peripheral codemyelination, which is also in line with previous findings (3). Further multi-modal investigations may be needed to confirm the pathophysiological basis of the alterations in MTR identified in this study, for example with the use of diffusion-weighted imaging, as demonstrated in previous studies of peripheral neuropathy (29)(30)(31).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the small sample size of our study does not allow a meaningful statistical assessment of differences between patients with and without DN. While this is a limitation, it should be considered that the development of DN has been shown to be a continuous process during which subclinical nerve damage can already be visualized and quantified with MRN imaging prior to the occurrence of clinical symptoms ( Groener et al, 2019 ; Morgenstern et al, 2021 ). In fact, the objective of this study was not to compare patients with and without DN, but to assess whether hsTNT is associated with a decrease in FA, that represents neurostructural deterioration mainly related to demyelination, and functional loss of proximal nerves at the upper limbs in patients with impaired glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis of this time-dependent dissociation between hyper- and hypoalgesia was recently studied in a prospective observational clinical study. Here, increased serum neurofilament light chain level (indicative of axonal injury) associated with hyperalgesia in T2DM patients with DPN while a decreased level of circulatory mRNA of myelin protein zero (indicative of demyelination) was associated with hypoalgesia [ 149 ]. Moreover, neurofilament light chain level correlated with quantitative sensory tests involving small unmyelinated C-fibers (warm detection, heat, and cold pain) whereas myelin protein zero mRNA level correlated with quantitative sensory tests involving myelinated A-δ and A-β fibers (mechanical sensitivity).…”
Section: Discussionmentioning
confidence: 99%